The Political Regime of the State According to 1918–1919 Lithuanian Constitutional Acts - Machovenko, Jevgenij; Valančienė, Dovilė (Teisė, 2022)
The article deals with identifying provisions of the 1918–1919 Lithuanian Constitutional Acts, which entrench the democratic political regime of the state. It discloses and assesses their dynamics, describes the nation’s sovereignty, elements of direct and representative democracy, and parliamentarism.
Keywords: Konstitucija; konstitucionalizmas; Lietuvos valstybės taryba; Steigiamasis Seimas; suverenitetas; viešoji valdžia; demokratija